1999
DOI: 10.1210/jc.84.9.3064
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment in Children with Short Stature Born Small for Gestational Age: 5-Year Results of a Randomized, Double-Blind, Dose-Response Trial

Abstract: The growth-promoting effect of continuous GH treatment was evaluated over 5 yr in 79 children with short stature (height SD score, less than Ϫ1.88) born small for gestational age (SGA; birth length SD score, less than Ϫ1.88). Patients were randomly and blindly assigned to 1 of 2 GH dosage groups (3 vs. 6 IU/m 2 body surface⅐day). GH deficiency was not an exclusion criterium. After 5 yr of GH treatment almost every child had reached a height well within the normal range for healthy Dutch children and in the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
207
3
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(233 citation statements)
references
References 26 publications
20
207
3
2
Order By: Relevance
“…Mean age at onset of puberty was normal for the patients in the study, consistent with what has been observed in other studies with hGH treatment (9,10,12,14,30), despite the fact that untreated SGA children have been reported in the past to have an earlier onset of puberty than normal children (19,31,32). The multivariate analysis in this study revealed that children who were older at the onset of puberty had a greater height gain at adult height.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mean age at onset of puberty was normal for the patients in the study, consistent with what has been observed in other studies with hGH treatment (9,10,12,14,30), despite the fact that untreated SGA children have been reported in the past to have an earlier onset of puberty than normal children (19,31,32). The multivariate analysis in this study revealed that children who were older at the onset of puberty had a greater height gain at adult height.…”
Section: Discussionsupporting
confidence: 90%
“…Short-to mid-term studies have demonstrated that catch-up growth can be induced by hGH administration, with height gains ranging from 1.1 to 2.6 SDS depending on the age of the children at treatment initiation, the hGH dosage used, and the duration of hGH therapy (7 -13). However, the pattern of hGH administration is still a matter of debate, as some authors favor continuous treatment (10) while others favor discontinuous treatment (9). Long-term results on adult height are scarce and discordant, with height gains ranging from 0.1 to 1.8 SDS in this patient group (14 -18).…”
Section: Introductionmentioning
confidence: 90%
“…Fat mass SDS adjusted for gender and height declined significantly, whereas the increase in lean body mass SDS adjusted for gender and height reflected the normal increase as a result of the increase in height (11). In a randomized clinical trial where prepubertal short SGA children were treated with 1 or 2 mg GH/m 2 per day, no significant differences in BMI SDS, BP, insulin levels, and lipid profile were found between the two GH dosage groups (8,10).…”
Section: Introductionmentioning
confidence: 91%
“…Metabolic effects of GH treatment in prepubertal short SGA children include the development of relative insulin resistance (IR) (8,9) with an improvement of blood pressure (BP) and lipid profile (10). Fat mass SDS adjusted for gender and height declined significantly, whereas the increase in lean body mass SDS adjusted for gender and height reflected the normal increase as a result of the increase in height (11).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria have previously been described (15,16). Height, weight, blood pressure, and serum lipids were measured before the start and during 4 years of GH treatment as previously described (17).…”
Section: Subjects and Study Designmentioning
confidence: 99%